Assessing efficacy and safety of replacement fluids in therapeutic plasma exchange: A systematic scoping review of outcome measures used. Issue 5 (21st June 2022) - Kohli, Ruchika; Geneen, Louise J.; Brunskill, Susan J.; Doree, Carolyn; Estcourt, Lise; Chee, Stephan E. J.; Al‐Bader, Raya; Sin, Wing Y. C.; MacCallum, Peter; Green, Laura
Abstract: Objective: The aim of this systematic scoping review is to identify and categorize the outcome measures that have been reported in clinical studies, where therapeutic plasma exchange (TPE) has been used as an intervention in any clinical settings, excluding thrombotic thrombocytopenic purpura (TTP). Methods: We searched electronic databases using a predefined search strategy from inception to October 9, 2020. Two reviewers independently screened and extracted data. Results: We included 42 studies (37 RCTs and 5 prospective cohort studies) grouped into six main categories (neurology, immunology, renal, rheumatology, hematology, and dermatology). Primary outcomes were defined in eight studies (19%, 8/42) and were categorized as efficacy (five studies) or patient reported outcomes (three studies). A power calculation was reported in six studies (75%, 6/8): five neurology studies (mainly patient reported outcomes) and a single immunological study (efficacy outcome). Disease‐specific efficacy outcomes were dependent on the clinical setting of the population receiving TPE. Most of the trials (43%, 18/42) were undertaken in patients with neurology conditions where clear, disease‐specific, clinical outcome measures were used, including neurological disability scales (11/18, 61%), change in neurological examination (9/18, 50%), and functional improvement scores (7/18, 39%). For other conditions, the reporting of disease‐specific outcomes was poorly reported. Safety outcomes were mainly related to replacement fluid type rather than being disease‐specific. The most common outcome reported was hypotension (19%, 8/42), and this was primarily in patients exchanged with albumin. Conclusion: Future clinical studies to determine which fluid replacement option is most efficacious and safe should use disease‐specific outcomes, as a trial in one therapeutic area may not necessarily translate to another therapeutic area. Patient reported outcomes are not universally reported for all disease areas. Safety measures focused primarily on fluid safety.